BCR Signaling in Chronic Lymphocytic Leukemia and Related Inhibitors Currently in Clinical Studies. (1st August 2013) - Robak, Tadeusz; Robak, Pawel
Abstract : Normal B lymphocytes receive signals from B-cell antigen receptor (BCR) that are triggered by binding of the BCR to an external antigen. Tonic signaling through the BCR provides growth and signals to chronic lymphocytic leukemia (CLL) cells, and plays an important role in the pathogenesis and progression of the disease. Antigen engagement of BCR is followed by intracellular recruitment and activation of BCR-associated kinases including spleen tyrosine kinase (Syk), Bruton's tyrosine kinase (Btk) and phosphatidylinositol 3-kinases (PI3K). Inhibition of signaling pathways downstream of the BCR induces disruption of chemokine-mediated CLL cell migration and cell killing. BCR signal transduction inhibitors represent a promising new strategy for targeted CLL treatment. A number of therapeutic agents have recently been developed with significant activity in CLL. The compounds that are currently investigated in patients with CLL include ibrutinib –inhibitor of Btk, fostamatinib-inhibitor of Syk and idelalisib (GS-1101) –a specific isoform of the PI3K (PI3K) inhibitor. The clinical activity of ibrutinib, GS-1101 and fostamatinib in patients with CLL is associated with marked lymphocytosis due to release of tumor cells from the lymph nodes into the peripheral blood. Further studies are ongoing with single agents and their combinations with other targeted and conventional therapies. This article will review the preclinical rationale of BCR signaling inhibitors in the treatment of CLL, and the clinical evidence supporting the use of these agents in CLL patients.